Second grave on the left - Jones, Darynda ([Charley Davidson novels, 2012)
When Charley is rudely awakened in the middle of the night by her best friend, who tells her to get dressed quickly and tosses clothes out of the closet at her, she can't help but wonder what Cookie's up to. Cookie explains that a friend of hers named Mimi disappeared five days earlier. Mimi left a clue, a woman's name. Meanwhile, Reyes Alexander Farrow, the Son of Satan, has left his corporeal body and is haunting Charley.